Investigation of some controllable factors that impact the stress state in cemented paste backfill - Doherty, J.P.; Hasan, A.; Suazo, G.H.; Fourie, A. (National Research Council of Canada, 2015)
This paper presents in-stope measurements of total stress and pore-water pressure at strategic locations within three underground stopes at the Raleigh mine site (Western Australia) that were filled with cemented paste backfill (CPB). The three stopes were very similar in shape. Key differences among the stopes were the filling and resting schedules, the barricade drainage systems used, and the cement content of the CPB. Data from the stopes are compared to determine which controllable factors most significantly influence barricade pressures during and after filling. The most significant factor was the scheduling of rest periods between filling, with even very short pauses in filling dramatically reducing the rate of increase of pore-water pressure and total stress with increasing height of fill.